Relationship of personal projects and meaningful orientations in youth and adolescence - Evgeniya Yu. Ryazantseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The problem of personal projects is brought to the forefront of scientific research by the very process of renewing a modern transitive society, which requires young people to be independent and responsible for their decisions and life choices. In this connection, the purpose of the research presented in the paper is to study the differences in the connections between the indicators of personal projects and the life-meaning orientations of the individual at the stages of adolescence and youth. The sample consisted of 148 people (64 boys and 84 girls aged 16 to 30). In use were used: the methodology Analysis of personal projects (B.R. Little in the adaptation of E.Yu. Ryazantseva), as well as the test of life-meaning orientations. Statistical analysis was performed in SPSS (version 22) using the Mann Whitney U test (for metric variables). The identification of links between metric indicators was carried out using correlation analysis (Spearmans coefficient). It was shown that a relationship was found between the indicators of personal projects (difficulty, visibility, control, responsibility, values, time adequacy, autonomy) and life-meaning orientations. At the age of 1617, young people are oriented towards outside support. For young people aged 18-25, the search for their identity becomes significant, where both the support of relatives and friends and their inner resources are important. At an older age (2630 years), the degree of individual independence in the implementation of their projects increases, the dependence on socio-cultural resources decreases, the number of connections between personal projects and indicators increases: goals in life, locus of control life.